Strategies for facing homesickness among non-local students in starting college at Airlangga University - Asdhar, Haztika Jihadania (Talenta Publisher, 2024)
This study describes strategies for dealing with homesickness among non-local students at the beginning of college at Airlangga University. The phenomenon of homesickness in students occurs due to difficulty adjusting to a new environment in the early days of college. This research uses a qualitative approach with grounded theory research methods. The data collection technique used in-depth interviews with informants to determine the criteria for first-semester students migrating to Airlangga University. The results of this study explain that students tend to experience homesickness when they are in a boarding house alone and have no activity. The strategy of Non-local students in dealing with homesickness is to understand the conditions encountered, communicate with family or friends, and find activities to fill their free time.